Nilai-Nilai Pendidikan Akhlak Dalam Buku “Me+God=Enough” Karya Ahmad Rifa’i Rif’an - Hasanah; Baharudin; Ida Faridatul Hasanah (Edu Berkah Khatulistiwa, 2026)
This study is motivated by the need to strengthen moral values as a response to the developments of modern times, which have impacted changes in individuals’ mindsets, behavior, and spiritual aspects. Therefore, learning resources are needed that can instill religious values in a systematic and practical manner, one of which is the book Me + God Enough by Ahmad Rifa’i Rif’an. This research aims to analyze the values of moral education contained in the book, which include morals toward Allah SWT, morals toward fellow human beings, and morals toward oneself. The study employs a qualitative approach using content analysis techniques through a systematic and in-depth examination of the text.The results show that the values of moral education toward Allah SWT include tawakal (trust in God), tauhid (monotheism), dzikrullah (remembrance of God), and taubat (repentance) as forms of strengthening faith. The values of moral education toward fellow human beings are reflected in the development of mutual respect, social awareness, empathy, and efforts to maintain harmonious social relationships, implemented through ukhuwah Islamiyah (Islamic brotherhood). Furthermore, the values of moral education toward oneself are manifested through the cultivation of mujahadah (self-discipline/struggle), qana’ah (contentment), patience, and syaja’ah (courage). Thus, this book contributes to supporting the internalization of spirituality-based moral education values that are relevant to the formation of religious character and ethical behavior in daily life.